Fertiliser best management practices for maize systems - Jat, Mangi Lal; Satyanarayana, T.; Majumdar, K.; Parihar, Chiter Mal; Jat, S.L.; Tetarwal, J.P.; Jat, Kumar Raj; Saharawat, Yashpal S. (2013)
Maize is an important crop for food and nutritional security in India. Strong market demand and resilience of maize to abiotic and biotic stresses have increased the area and production of maize in the country over the past decade. Productivity of maize, however, has not increased proportionately and significant yield gaps are evident across maize growing areas in the country. Maize is an exhaustive crop and removes large amounts of plant nutrients from the soil to support high biomass production. The 4R Principles of applying right source of nutrients, at the right rate, at the right time and at the right place is expected to increase nutrient use efficiency, productivity and farm profit from maize production and provides opportunity for better environmental stewardship of nutrients. Adaptation of 4R Principle-based site-specific nutrient management decision support tools provides the opportunity for large-scale adoption of improved nutrient management across maize ecologies.